2022
DOI: 10.1144/jgs2021-072
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb age constraints on the protolith, cooling and exhumation of a Variscan middle crust migmatite complex from the Central Iberian Zone: insights into the Variscan metamorphic evolution and Ediacaran palaeogeographic implications

Abstract: The Figueira de Castelo Rodrigo – Lumbrales Anatectic Complex (FCR-LAC) located in the Central Iberian Zone of the European Variscan Belt is delimited by two shear zones, which have been interpreted as constraining its exhumation. New U-Pb zircon and apatite ages for the migmatites allowed to obtain a peak metamorphic age of the anatectic complex (316.8±2.0 Ma), and to estimate fast cooling (7-54 °C/Ma) and fast exhumation (0.2-1.3 mm.a-1) after a vertical displacement of ca. 6-9 km.Our results show a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…iv) The relative low proportion of Mesoproterozoic zircons in the OMZ and the WALZ-CZ, suggesting proximity to the West African Craton (WAC). The opening of the system to Stenian-Tonian zircons is only statistically significant in the Early Ordovician (both in Iberia and North Africa) and probably indicates the influence of the Arabian-Nubian shield (ANS) (Altumi et al, 2013;Avigad et al, 2003;Casas and Murphy, 2018;Ferreira et al, 2022;Goodge et al, 2004;Keppie et al, 1998;Lains Amaral et al, 2022;Linnemann et al, 2004;Williams et al, 2012). In the Ediacaran and the Cambrian, the relatively minor subpopulation of these grains may be explained by assuming the long-distance transport of sediments and the high degree of sediment mixing as a means of dilution of the proportion of these ages (Avigad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iv) The relative low proportion of Mesoproterozoic zircons in the OMZ and the WALZ-CZ, suggesting proximity to the West African Craton (WAC). The opening of the system to Stenian-Tonian zircons is only statistically significant in the Early Ordovician (both in Iberia and North Africa) and probably indicates the influence of the Arabian-Nubian shield (ANS) (Altumi et al, 2013;Avigad et al, 2003;Casas and Murphy, 2018;Ferreira et al, 2022;Goodge et al, 2004;Keppie et al, 1998;Lains Amaral et al, 2022;Linnemann et al, 2004;Williams et al, 2012). In the Ediacaran and the Cambrian, the relatively minor subpopulation of these grains may be explained by assuming the long-distance transport of sediments and the high degree of sediment mixing as a means of dilution of the proportion of these ages (Avigad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These scarce igneous remnants of the magmatic arc occur in parallel with large volumes of synarc-and back-arc-related sediments (the so-called Série Negra [SN] Formation). The OMZ is bounded to the North by the CIZ, whereas the Douro-Beiras Supergroup features the oldest outcrops, including the Beiras and Douro Groups, which consist of Neoproterozoic-to-early-Cambrian metasedimentary rocks (Ferreira et al, 2022;Medina et al, 1998;Meireles, 2020;Sousa and Sequeira, 1993).…”
Section: The Pre-variscan Iberian Massifmentioning
confidence: 99%
See 1 more Smart Citation
“…The pegmatites of the FA field were emplaced within a belt of metasedimentary rocks in contact to the south with a major anatectic dome and bounded by sinistral strike-slip shear zones; the dome mostly consists of syntectonic two-micabearing leucogranites and migmatites, referred to as the Figueira de Castelo Rodriguo-Lumbrales (FCL) complex (Díez Fernández and Pereira, 2016;Ferreira et al, 2019Ferreira et al, , 2020Ferreira et al, , 2022 (Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%
“…319-311 Ma, zircon U-Pb;Ferreira et al, 2019), as well as U-Pb zircon ages of associated migmatites (ca. 344-315 Ma;Ferreira et al, 2020Ferreira et al, , 2022. Roda-Robles et al (2009, thus, concluded for an absence of genetic connection between leucogranites from the FCL complex and Li-mineralized pegmatites from the FA field, and proposed a genetic link with non-outcropping late-to post-orogenic granites.…”
Section: Introductionmentioning
confidence: 99%